1991
DOI: 10.1111/j.1745-4506.1991.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oven Temperature and Time on the Losses of Some B Vitamins in Roasted Beef and Pork

Abstract: The study was carried out to enumerate the effect of thermal process variables on the losses of some B vitamins and moisture from roasted beef and pork of various sizes in a hot air oven. The roasting temperature and time of both samples were varied from 100‐160°C and 15 min to 1 h, respectively. Thiamin losses were between 20‐40% (0.116‐0.232 mg/100 g) in pork and between 15‐25% (0.006‐0.011 mg/100 g) in beef at the same period. The loss of riboflavin was between 10‐25% (0.019‐0.047 mg/100 g) in beef when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…Awonorin and Rotimi (1991) found a strong agreement between moisture reduction and loss of thiamin, riboflavin and niacin in beef and pork roasted in great quantities. Time-temperature combination also played a significant role in vitamin losses, since it is directly related to moisture loss when meats are cooked were.…”
Section: Evaluation Of Na Stabilitymentioning
confidence: 71%
See 1 more Smart Citation
“…Awonorin and Rotimi (1991) found a strong agreement between moisture reduction and loss of thiamin, riboflavin and niacin in beef and pork roasted in great quantities. Time-temperature combination also played a significant role in vitamin losses, since it is directly related to moisture loss when meats are cooked were.…”
Section: Evaluation Of Na Stabilitymentioning
confidence: 71%
“…However, such a process can interfere with the stability of certain nutrients, such as vitamins (Hill 1994;Selman Depending upon the temperature, time and the type of processing, meats are susceptible to losses of moisture and vitamins, especially the water soluble. Despite efforts to improve the quality of processed products, especially meats, little information is available on the variables which influence vitamin stability (Awonorin and Rotimi 1991). Niacin generally shows excellent stability to heat and light in the entire range of pH of foods.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of thiamin retention (Y) in different types of meat samples was correlated empirically with relevant processing parameters (Awonorin & Rotimi, 1991), namely: (a) mass fraction of moisture content (XI) on wet basis after a predetermined time of heat processing; (b) cooking temperature (X,) in "C: (c) mass of sample (X,) in grams and (d) cooking time (X,) in minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent investigation on beef and pork roasts, Awonorin & Rotimi (1991) enumerated the effect of some heat processing variables on B-vitamin losses in freshly roasted beef and pork. In that study, vitamin retention was shown to increase with decreased temperature and time, and the sample size increased or ratio of the mass of sample to its exposed area increased.…”
Section: Dcpartmcnt Of Food Scicncc and Tcchnology Andmentioning
confidence: 99%
“…This could be due to the higher weights of the liver samples, because for preparation the same aluminum dishes were used. Awonorin and Rotimi (1991) reported vitamin retentions in meat samples were enhanced by increased thickness or higher ratio of mass of sample to exposed surface area. Fox et al (1993a) however, examined the effect of reductant level in skeletal muscle and liver on the rate of loss of thiamin due to ␥-radiation.…”
Section: Vitamin Retention After Heatingmentioning
confidence: 98%